Phylogenetic relationships and review of the species of Auricularia (Fungi: Basidiomycetes) in Colombia (2011)
ABSTRACT: The phylogenetic relationship of the species of the genus Auricularia and its allied taxa were investigated using the internal transcribed spacer (ITS) sequences of nuclear DNA. A molecular phylogenetic tree constructed using a total of 17 samples representing fi ve species and two outgroups indicates that the species of Auriculariaform a monophyletic group. Within the genus Auricularia, A. mesenterica is basal and the remaining Auricularia species form three clades; the fi rst clade consists of A. auricula-judae; the second, of A. fuscosuccinea; and the third, of A. polytricha.